Strategic maps of indicators as a management practice tool - G.M. Tarasyuk; O.A. Donetsk; L.O. Gorshkova (Економіка, управління та адміністрування)
The article discusses the theoretical bases for the formation of strategic maps of indicators and determines their importance for the implementation of any organization's strategy. The author carries out the analysis of the existing balanced systems of indicators, which were researched by leading scientists and used in the practice of management. The importance of the interconnection of the system of indicators on different levels of the hierarchy is proved. It is proved that consistency between different indicators is determined by the nature of cause and effect relationships, and is achieved by harmonizing, balancing and coordinating the definitions and classifications that underlie their calculation. The knowledge of the content of indicators and the forms of relationships between them will allow to create a multifaceted reflection of the set of processes planned in business. In addition, the balanced system of indicators performs certain functions (planned, controlling, stimulating, regulating). The peculiarities of forming thestrategic maps of indicators for state institutions and organizations are considered. The integrated model of the balanced system of indicators for planning the potential of a manufacturing enterprise is also presented.